Effect of Concentration and Suspension Agent (HPMC) on Properties of Coal Gangue and Fly Ash Cemented Filling Material. (8th February 2021) - Yang, Baogui; Jin, Junyu; Yin, Xindong; Wang, Xiaoyu; Yang, Hongliang
Abstract : Cemented coal gangue-fly ash backfill (CGFB) mixtures are utilized as the filling materials for backfilling the underground openings in coal mines. The freshly prepared CGFB slurries are commonly transported into the gobs through a pipeline. The mixture ratio of slurry concentration and suspending agent (HPMC) plays an essential role in transporting the slurry to goaf smoothly and efficiently. In this paper, the influence of slurry concentration and HPMC on the performance of coal gangue-fly ash cemented filling material was studied based on the response surface method. The prediction model of CGFB slurry slump flow, segregation rate, and bleeding rate was constructed. It is concluded that the segregation rate and slump flow of slurry are more sensitive to the variation of concentration. On the other hand, the bleeding rate of slurry is more sensitive to the change of HPMC content. Based on the established model, the reasonable mix proportion range of slurry concentration and suspending agent (HPMC) was obtained. In addition, three new CGFB mixtures have been tested, and the experimental results are in good agreement with the predicted values.